Evaluasi Efektivitas Metode F-A-S-T Flipbook dalam Meningkatkan Deteksi Dini Stroke: Studi Pendidikan Pra-Rumah Sakit di Indonesia - Cecilya Kustanti; Linda Widyarani (Ners Jurnal Keperawatan, 2023)
Stroke remains a prominent cause of disability and high mortality rates, particularly within Indonesia. Timely intervention during the critical phases of a stroke can mitigate disabilities and fatalities. Health education stands as a pivotal strategy for implementing health promotion and disease prevention initiatives. This study seeks to evaluate the efficacy of employing the flipbook F-A-S-T method as an educational tool to enhance early stroke detection utilizing the F-A-S-T media in a prehospital context. Utilizing a quantitative approach and a pre-experimental design, specifically a one-group pre-post test design, this research applies purposive sampling for participant selection. Initial knowledge assessments yielded a mean pretest score of 72.88±2.818. Following the intervention, the mean posttest score increased to 82.24±1.640. Statistical analysis indicated a p-value of 0.000, signifying a significant difference in knowledge levels before and after the educational intervention. The study findings strongly suggest that the implementation of flipbook F-A-S-T methods as an educational medium substantially enhances knowledge regarding the early detection of stroke utilizing the F-A-S-T method in a prehospital setting. This underscores the potential of such educational tools in improving public awareness and preparedness in the context of stroke, ultimately contributing to more favorable outcomes and reduced stroke-related disability and mortality rates.